Mengkaji Hakekat Misi Inklusif Yesus Berdasarkan Injil Lukas Dan Aplikasinya Bagi Misi Masa Kini - Yesri Talan (Manna Rafflesia, 2020)
Luke introduces Jesus' inclusive ministry to preach the gospel, fellowship and serve the excluded. In this context, people who are paralyzed, blind, deaf, poor, tax collectors who are considered sinful, they are the center of His attention. By observing the current mission which is oriented to the church planting mission, it is necessary to transform. The intended transformation is to change the motive of the church planting mission to a mission that is not an anthropocentric mission but a mission to glorify God. The method used in writing this scientific paper is a qualitative method. Literature study and the Bible as the main source in explaining. Aside from literature and Bible study sources, the sources obtained are based on facts from field observations.